The impact of Saccharomyces cerevisiae stimulation on various physiological indicators of oats (Avena sativa) exposed to salinity - HIBA FOUAD ABDULFATAH; ENAS FAHD NAJI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Abdulfatah HF, Naji EF. 2023. The impact of Saccharomyces cerevisiae stimulation on various physiological indicators of oats (Avena sativa) exposed to salinity. Biodiversitas 24: 6753-6760. The objective of the current study is to examine the effects of different levels of salinity, specifically 0, 2.5, and 4.5 ds m-1(S1, S2, S3), on diverse physiological parameters in two principal oat cultivars (Avena sativa L.), Pimula (A1), and Genzania (A2), priming with Saccharomyces cerevisiae for 24 hours at a concentration of 0 and 6 g.L-1. The study employed a completely randomized design with three repetitions for each treatment and was conducted at the laboratory of the College of Science, University of Anbar. The Genzania cultivar that was not stimulated with yeast demonstrated the highest percentage of total chlorophyll content (2.28 mg. g. plant-1), statistically significant (P?0.05) compared to the lowest rate recorded by the Pimula cultivar (1.94 mg. g. plant-1). While no significant differences appeared between both cultivars stimulated with yeast under the influence of the salinity concentrations, the S2 treatment had the highest rate and significantly more than the S3 treatment. This demonstrates increased tolerance of the yeast priming cultivars to salinity treatment. The A2 cultivar was characterized by the highest rate of proline in plants stimulated and not stimulated with yeast, with significant differences from the A1 cultivar. However, the S3 treatment had the highest rate of proline (20.96?mole g plant-1) in the stimulated plants, with a higher significance than treatment S2. There was a statistically significant in the electrolyte leakage rate between the non-stimulated cultivars. In contrast, no significant differences appeared for the plants stimulated with yeast, indicating an increase in their tolerance to salinity. Priming seeds with yeast extract has been shown to improve important physiological characteristics in plants, such as total chlorophyll content, proline content, and electrolyte leakage, indicating the effectiveness of yeast in increasing plant resilience to salt stress.